Integração e cooperação territorial da Tríplice Fronteira de Foz do Iguaçu (Brasil), Puerto Iguazú (Argentina) e Ciudad Del Este (Paraguai) - Marques, Josiel Alan Leite Fernandes (2017)
The Triple Border of Brazil, Argentina and Paraguay, which circumscribes the territorial boundaries of the cities of Foz do Iguaçu, Puerto Iguazú and Ciudad del Este, respectively, has been accentuated by the international prominence in the media in the 1990s with the suspicion of that there were islamic terrorists in the territory. However, its process of constitution is old and dates back to the sixteenth century, especially to the first contact of the european, driven by the ideas of globalization, with the Guarani indians. The not always friendly relations of these two peoples corroborated in the establishment of dynamic integrative and cooperative processes in the political, social, cultural and economic sectors that culminated in the creation of mechanisms of integration and cooperation, such as the Technical Instances, in the forms of Commissions, Committees and ratification of bilateral and trilateral Treaties and international Agreements between the three Nations. This research aims at analyzing the process of territorial integration and cooperation in the Triple Border and in the cross-border territorialities of Brazil, Argentina and Paraguay, and does this by relating these territorialities between globalization and territorial integration and cooperation; in identifying the mechanisms: Technical Instances, Agreements, Treaties, Minutes and bi and trilateral declarations of integration and cooperation between the countries involved; and historicizing these mechanisms related to geopolitics with territorial development. With the application of bibliographic and documentary research in physical and electronic media and databases of the Mercado Comum do Sul – Mercosul, the Governo Federal, the Instituto Brasileiro de Geografia e Estatísticas – IBGE, the Companhia de Pesquisa de Recursos Minerais – CPRM, the Prefeitura de Foz do Iguaçu, the Municipalidad of Puerto Iguazú, the Municipalidad de Ciudad del Este, the Usina de Itaipu Binacional, the Ministério das Relações Exteriores – MRE and the Embassies of the three countries, the Technical Instances of integration and cooperation were identified and delimited, as well as the Agreements and Treaties ratified and limited to the Triple Border. The justification is based on the observation of these cross-border territorialities, where the flow of people, goods, services and capital is intense and diverse, and therefore requires in-depth studies characterizing the geographical, historical and political elements capable of recognizing the obstacles and potentialities integrators and cooperators. The problem leads us to respond if the Triple Border is part of a globalizing process with glocalised and interrelated implications for the circuits of territorial integration and cooperation, and which governmental acts prove this integration and cooperation in the territory of the Triple Border. The structure of this research is organized in three sections, in addition to this introduction and the final considerations: the first exposes the state of the art of the betting themes according to the bibliographic production; the second refers to the characterization of the area of study and the historical process of formation of the Triple Border; and the third, identifies and historicizes the mechanisms of integration and cooperation created bi and trilaterally.